2021
DOI: 10.3390/ijms22073796
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Sphingolipid Metabolizing Enzymes in Spontaneously Hypertensive Rats: A Possible Substrate for Susceptibility to Brain and Kidney Damage

Abstract: Alterations in the metabolism of sphingolipids, a class of biologically active molecules in cell membranes with direct effect on vascular homeostasis, are increasingly recognized as important determinant in different vascular disorders. However, it is not clear whether sphingolipids are implicated in the pathogenesis of hypertension-related cerebrovascular and renal damage. In this study, we evaluated the existence of possible abnormalities related to the sphingolipid metabolism in the brain and kidneys of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Of interest, plasma Cer levels are increased in hypertension ( Spijkers et al, 2011 ; Mielke et al, 2019 ). However, it has recently been observed that in stroke-prone hypertension model rats the expression of SPTLC1 and SPTLC2 are decreased in the brain compared to wild-type rats ( Pepe et al, 2021 ). Moreover, the depletion of SPTLC2 in mice showed that C 16:o -, C 24:0 -, and C 24:1 -Cer were observed essentials in vascular and blood pressure homeostasis, and establish the endothelium as a crucial source of plasma Cer ( Cantalupo et al, 2020 ).…”
Section: Stroke and Ceramide Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, plasma Cer levels are increased in hypertension ( Spijkers et al, 2011 ; Mielke et al, 2019 ). However, it has recently been observed that in stroke-prone hypertension model rats the expression of SPTLC1 and SPTLC2 are decreased in the brain compared to wild-type rats ( Pepe et al, 2021 ). Moreover, the depletion of SPTLC2 in mice showed that C 16:o -, C 24:0 -, and C 24:1 -Cer were observed essentials in vascular and blood pressure homeostasis, and establish the endothelium as a crucial source of plasma Cer ( Cantalupo et al, 2020 ).…”
Section: Stroke and Ceramide Metabolismmentioning
confidence: 99%
“…These data could indicate a possible implication of KDR activity or up-regulation of CerS in the evolution of ischemic lesions; therefore, more investigations should be addressed. Interestingly, recent work has demonstrated a reduction of KDR expression in spontaneously hypertensive rat stroke-resistance in the brain ( Pepe et al, 2021 ).…”
Section: Stroke and Ceramide Metabolismmentioning
confidence: 99%
“…Following ischemic stroke, regulation of S1PR2 antagonist and knockout of S1PR2, which is involved in endothelial activation during acute vascular inflammation injury and increases pro-inflammatory cytokines ( 165 ), led to a decrease in infarct ratio and cerebral edema ratio, and better neurological scores in mice cell models of stroke ( 108 , 166 ). Inhibition of SphK1, a kinase involved in S1P generation and has an essential role in regulating inflammation, also reduced infarct volumes and improved neurological deficits after stroke in mice model by reducing the expression of TRAF2 and NF-κB ( 108 , 167 ). Mouse brain tissue and human patients with acute ischemic stroke showed a marked increase in long-chain ceramides and specific ceramide species, which correlated with poor functional outcomes ( 168 ).…”
Section: Sphingolipids’ Involvement In Inflammation and Cardiovascula...mentioning
confidence: 99%
“…Phosphatidyl choline (PC) dissociates into arachidonic acid and LysoPC; their elevated levels can induce endothelial dysfunction, which leads to hypertension (Dietrich et al, 2016). Abnormal lipid metabolism was found in spontaneously hypertensive rat (SHR) (Pepe et al, 2021). Moreover, SHR had higher levels of LysoPCs (22:4; 22:5; 22:6; O‐18:0), phosphatidic acids [PAs (16:0/16:0)], and LysoPAs (0:0/18:0) (Tian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%